Variability of Î²-asarone in In-vitro Raised and Ex-situ Grown Acorus calamus Linn - Mazher, Farheen; Singh, Pratibha (Indian Forester, 2012)
The oil content in rhizomes of four-month old tissue culture raised and field grown Acorus calamus plants were extracted by soxhlet extraction method and analyzed by Gas Liquid Chromatography. The main chemical component found was Î²-asarone. Percentage of averageminimum Î²-asarone content was found 88.40% in the rhizome of 5 month old tissue cultured plants. The maximum Î²-Asarone average content 88.74% was recorded from rhizomes of twelve month old plants. Î²-asarone content varied between 64.27% of five month old plants and 82.61% in 12 months old plants. The leaves of in-vitro raised A. calamus showed minimum Î²-asarone content with an average of 79.82% in five monthold plants whereas maximum Î²-asarone averagecontent 81.71% was recorded from twelve monthold plants.